Screening of Free Carnitine and Acylcarnitine Status in Children With Familial Mediterranean Fever - Ertuğrul KIYKIM,; Ayşe Çiğdem AKTUĞLU ZEYBEK,; Kenan BARUT,; Tanyel ZÜBARİOĞLU,; Mehmet Şerif CANSEVER,; Şeyda ALSANCAK,; Özgür KASAPÇOPUR, (Archives of Rheumatology, 2016)
Objectives: This study aims to demonstrate the patterns of free carnitine (FC) and acylcarnitine (AC) esters in familial Mediterranean fever (FMF) patients. Patients and methods: A total of 205 patients (106 males, 99 females; mean age 131.3±52.1 months; range 24 to 254 months) with FMF and 50 healthy controls (27 males, 23 females; mean age 125.7±49.6 months; range 32 to 217 months) were enrolled. Fasting dried blood samples were taken for showing FC and AC ester levels with tandem mass spectrometry from both patients and controls. Results: Screening of AC profile revealed increased FC, 3-hydroxypalmitoylcarnitine (C16-OH), and 3-Hydroxy octadecanoylcarnitine (C18:2-OH) carnitine levels, while decreased acetyl-carnitine (C2), propionyl-carnitine (C3), butyryl-carnitine (C4), tiglyl-carnitine (C5:1), hexanoyl-carnitine (C6), octanoyl-carnitine (C8), decenoylcarnitine (C10:1), decadienoylcarnitine (C10:2), malonylcarnitine (C3DC), methylmalonylcarnitine (C4DC), glutarylcarnitine (C5DC), hexadecenoylcarnitine (C16:1), 3-Hydroxy butyrylcarnitine (C4-OH), and 3-Hydroxy oleylcarnitine (C18:1-OH) carnitine levels in FMF patients compared to controls. Total AC levels (p<0.001) and AC to FC ratio (p<0.001) were also lower in FMF patients than the controls. Conclusion: In this study, we were able to detect some of the AC profile variations in FMF patients; however, usage of carnitine in all patients with FMF is not recommended since we were not able to demonstrate secondary carnitine deficiency in FMF patients of this study.